Survei Pola Kuantitas Peresepan Antibiotik di Tiga Rumah Sakit di Indonesia dengan Penatagunaan Antimikroba Digital - Natadidjaja, Ronald Irwanto; Lekok, Widyawati; Ariyani, Aziza; Adlani, Hadianti; Adianto, Raymond; Maharani, Ronaningtyas; Sumarsono, Hadi; Yenny, Yenny; Samira, Jihan; Hairunisa, Nany; Amalia, Husnun; Faradila, Meutia Atika; Fadilah, Tubagus Ferdi; Kalumpiu, Joice Viladelvia; Yuliana, Yuliana; Mulyani, Sri; Anggiat, Desi; Marja, Triyoko Septio; Pertiwi, Iin Indra; Dianawati, Dianawati; Legoh, Grace Nerry; Rantung, Alvin Lekonardo (Jurnal Biomedika dan Kesehatan, 2025)
Background Antimicrobial Stewardship Program (ASP) is very essential. There are three categories of antimicrobial agents as recommended by WHO: Access, Watch and Reserve. e-RASPRO, a digital ASP model, may alter antibiotic prescribing patterns by prioritizing Access category antibiotic prescribing. Methods Our manuscript presented a quantitative survey on antibiotic prescribing patterns within 3 months and 9 months before and after implementing digital electronic-RASPRO (e-RASPRO) in three Indonesian hospitals, utilizing retrospective inpatient data. This analysis included the appropriateness of empirical antibiotic prescribing and the quantity of antibiotic prescribing based on each category. Results In the first 3 months, we found that 90.16%, 83.98%, and 81.15% of patients were included in Type 1 Risk Stratification. The appropriateness of initial empirical antibiotic prescribing with the digital guideline on antimicrobial use of e-RASPRO in three hospitals was 81.59%, 76.09% and 24.48%, respectively. Within 9 months after implementing e-RASPRO in Hospital A and B and within 3 months in Hospital C, there was a trend of reduced quantity of Watch category antibiotic prescribing of 54.93% (-58.86% per inpatient), 21.11% (-9.97% per inpatient), and 8.59% (-4.15% per inpatient), respectively. There was a 12.42% (+2.61 % per inpatient) and 223.17% (+268.83% per inpatient) increase in the quantity of Access category antibiotic prescribing in Hospitals A and B, while in Hospital C, the quantity decreased by 6.81% (-2.29% per inpatient).   Conclusions There are changes in antibiotic prescribing patterns, particularly in the antibiotics included in the Watch and Access categories following the implementation of e-RASPRO. The relationship between digital antimicrobial stewardship use and the results still needs further research.